Ecosystem Services Valuation for Estuarine and Coastal Restoration in Florida - Susanna Blair; Carrie Adams; Tom Ankersen; Maia McGuire; David Kaplan (EDIS, 2018)
Throughout Florida’s history, humans have altered the coastlines, leading to large-scale degradation of coastal ecosystems. This has led to the loss of associated ecosystem services, including products such as food and timber, and processes like coastal protection and disease control. Unfortunately, ecosystem restoration efforts have not always been a priority for coastal management. This 10-page literature review surveys the available ecosystem-service valuation literature for five of Florida’s coastal natural communities—oyster reefs, beach dunes, mangrove forests, seagrass beds, and salt marshes—to facilitate the quantification of ecosystem services to provide a better measure of the full impact of restoration efforts. Written by Susanna Blair, Carrie Adams, Tom Ankersen, Maia McGuire, and David Kaplan, and published by the UF Department of Sea Grant, January 2015. (UF/IFAS photo by Tyler Jones)